Development of a Novel Test for Simultaneous Bacterial Identification and Antibiotic Susceptibility. (30th October 2016) - Faro, Jonathan; Mitchell, Malika; Chen, Yuh-Jue; Kamal, Sarah; Riddle, Gerald; Faro, Sebastian
Abstract : Background . Elucidation of a pathogen's antimicrobial susceptibility requires subculture after the organism is first isolated. This takes several days, requiring patients to be treated with broad-spectrum antibiotics. This approach contributes to the development of bacterial resistance. Methods . Microtiter wells were coated with a polyclonal antibody targeting the pathogen of interest. Bacterial suspensions were added in the presence/absence of selected antibiotics. After washing, captured bacteria were detected. Findings . Group B streptococcus (GBS), Enterococcus faecalis, and Neisseria gonorrhoeae were each detected at 10 5  bacteria/mL following a 20-minute incubation period. Susceptibility to select antibiotics was discernable following a 6-hour incubation period (GBS and Enterococcus ). Sensitivity was increased to 10 −2  bacteria/mL for GBS, 10 −1  bacteria/mL for E. faecalis, and 10 1  bacteria/mL for N. gonorrhoeae following 18–24-hour culture. Conclusion . This novel assay allows for the highly sensitive and specific identification of a pathogen and simultaneous determination of its antimicrobial susceptibility in a reduced time.